2020
DOI: 10.1002/wer.1347
|View full text |Cite
|
Sign up to set email alerts
|

A high‐rate anaerobic biofilm reactor for biomethane recovery from source‐separated blackwater at ambient temperature

Abstract: Anaerobic bioreactors for source-separated blackwater are mostly operated at low organic loading rates (OLRs) due to low biodegradability and the potential of ammonia inhibition. In this study, an anaerobic biofilm reactor having conductive carbon fibers as the media was investigated for the high-rate treatment of blackwater collected from vacuum toilets. The bioreactor was operated at different OLRs ranged from 0.77 to 3.01 g COD/L-d in four stages for a total operating period of ~ 250 days. With the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 82 publications
(141 reference statements)
0
1
0
Order By: Relevance
“…For instance, a recent study [17] reported a granular activated carbon (GAC) biofilter that could remove 94% chemical oxygen demand (COD) from greywater for a hydraulic retention time (HRT) of 2.4 h. Interestingly, energy recovery potential from greywater with anaerobic biotechnologies has been rarely investigated. Anaerobic bioprocess, such as anaerobic digestion, is usually known to be more effective for high-strength wastewater [18][19][20]. However, compared to anaerobic digestion, microbial communities in emerging microbial electrochemical systems, such as microbial fuel cells (MFCs), microbial electrolysis cells (MECs), can provide effective removal of organics from dilute wastewater, including domestic sewage [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a recent study [17] reported a granular activated carbon (GAC) biofilter that could remove 94% chemical oxygen demand (COD) from greywater for a hydraulic retention time (HRT) of 2.4 h. Interestingly, energy recovery potential from greywater with anaerobic biotechnologies has been rarely investigated. Anaerobic bioprocess, such as anaerobic digestion, is usually known to be more effective for high-strength wastewater [18][19][20]. However, compared to anaerobic digestion, microbial communities in emerging microbial electrochemical systems, such as microbial fuel cells (MFCs), microbial electrolysis cells (MECs), can provide effective removal of organics from dilute wastewater, including domestic sewage [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%